Characteristics of colorectal cancers among Alaska Native people before and after implementing programs to promote screening. (September 2021) - Nash, Sarah H.; Britton, Carla; Redwood, Diana
Highlights: Alaska Native people have the highest rate of colorectal cancer (CRC) globally. We examined changes in the descriptive epidemiology of CRC among AN people concurrent with increases in screening prevalence. CRC incidence increased among AN people aged < 50 years; there were modest declines in AN people > 50 years old since 2000. AN CRC mortality rates declined 1990 - 2004, but have been increasing steadily since that time. There were no differences in age at diagnosis, tumor size, stage distribution, or survival comparing 2000–2008 with 2009–2017. Intensified efforts are required to reduce the CRC burden in this high-risk population. Abstract: Background: Alaska Native (AN) people have the highest rates of colorectal cancer (CRC) globally. Increasing CRC screening has been effective in reducing CRC-related morbidity and mortality in other populations. Objective: To examine recent descriptive epidemiology and longer-term CRC trends among AN people. To determine any changes in the descriptive epidemiology of CRC among AN people concurrent with increases in screening prevalence. Methods: We estimated age-specific CRC incidence and mortality rates 2000−2017. To examine longer-term trends in incidence and mortality 1990–2017, we conducted Joinpoint regression analyses of three-year rolling average incidence and mortality rates. We calculated descriptive statistics for two time-periods: 2000−2008, and 2009−2017. Finally, we examined five-year survival probability. Results: CRC incidence increased over time (1990–2017) among AN people aged less than 50 years, while there were modest declines in AN people older than 50 years old since 2000. Overall, AN CRC mortality rates declined between 1990 and 2004, but have been increasing steadily since that time. Comparing 2000−2008 with 2009−2017 we observed no difference in CRC incidence and mortality, age at diagnosis, tumor size, tumor location, or stage distribution. Survival analyses indicated no change in hazard of death between 2004−2008 and 2009−2017 (HR 1.02, 95 % CI: 0.74, 1.38, P = 0.93). Conclusions: Colorectal cancer prevention and control efforts across the Alaska Tribal Health System have not yet resulted in reduced mortality rates, or induced earlier stage migration. Policy summary statement: Intensified efforts will be necessary to reduce the burden of CRC among this high-risk population. Continued and increased focus on primary and secondary prevention efforts is warranted.